2013
DOI: 10.1007/s10548-013-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Preattentive Processing of Facial Expressions: An ERP Study

Abstract: To investigate gender differences in pre-attentive processing of facial expressions we recorded the expression mismatch negativity (EMMN) in the deviant-standard-reverse oddball paradigm. For female participants, sad faces elicited larger EMMN than happy faces, but this difference disappeared in the left hemisphere. For male participants, EMMN was not modulated by facial expressions, regardless of in the left or right hemispheres. While the source analysis indicated that for both genders prefrontal activations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 64 publications
3
34
0
1
Order By: Relevance
“…Previous findings have indicated that schematic faces may be useful for clinical study and application because of their simplicity compared to actual human faces (Wright et al, 2002). Although schematic emotional faces have been used in several studies (Chang et al, 2010; Xu et al, 2013) and similar vMMN results have been reported with real faces, it is necessary to use real faces to further investigate this issue.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous findings have indicated that schematic faces may be useful for clinical study and application because of their simplicity compared to actual human faces (Wright et al, 2002). Although schematic emotional faces have been used in several studies (Chang et al, 2010; Xu et al, 2013) and similar vMMN results have been reported with real faces, it is necessary to use real faces to further investigate this issue.…”
Section: Discussionmentioning
confidence: 94%
“…As presented in a previous study conducted by this research group (Xu et al, 2013), to reduce the effect of low-level features, 54 different schematic faces with neutral, sad, and happy expressions were used, and 18 individual schematic faces were included for each stimulus type (see an example in Figure 1A). Modulated by changing the shape of and the distance between the facial features, each type of stimulus included 18 models.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies, however, report sex differences in ERPs during emotion processing, including emotion in the voice (e.g., Schirmer et al, 2007) and in the face (e.g., Xu et al, 2013), suggesting that females may be more sensitive to emotional signals. For example, females process emotion in the voice more automatically than males (Schirmer and Kotz, 2003).…”
Section: Neuronal Mechanisms For Empathymentioning
confidence: 99%
“…They have been extensively applied to the study of attention to emotional stimuli such as fear (12), anger (13), and emotion-word Stroop effect (14), and have been effective in other psychological and cognitive studies (15,16). Attention bias is preferentially sustained by affective significance stimuli (17), which can be recorded by P200 and P300 registered in the frontal and parietal areas of the brain.…”
Section: Introductionmentioning
confidence: 99%